Energy-Efficient Attribute-Aware Data Aggregation Using Potential-Based Dynamic Routing in Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2014)
Sensor nodes gather data in Wireless Sensor Networks (WSNs), which is pieced together at the sink. Most of the energy of SNs is consumed in transmission and reception of the data packets. Reduction in transmission of data packets greatly improves the lifetime of WSNs as it not only reduces the energy of transmitting nodes but also of the receiving nodes. Since the network consists of low-cost nodes with limited battery power, power efficient methods must be employed for data gathering and aggregation in order to achieve long time network usage. Attribute-aware data aggregation uses the concept of packet attribute, can make the packets with the same attribute spatially convergent as much as possible and improves efficiency of data aggregation. To improve network efficiency, the proposed mechanism focuses on efficient data aggregation in tree based network by constructing energy efficient duty cycled data aggregation trees. In this method the number of transmissions is reduced and the energy consumption also get reduced.